Penerapan Metode Bermain Tradisional Engklek dalam Meningkatan Keterampilan Motorik Kasar pada Anak Usia Dini RA Az Zahra Sukahaji - Vera Yuliani; Vera Oktavia; Vera Siti Magfiroh; Uswatur Rohmah; Uswatun Hasanah (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
Gross motor development in early childhood plays an important role in supporting their physical abilities, balance, and motor coordination. One method that can be used to improve gross motor skills is through traditional games. This study aims to analyze the application of traditional engklek games in improving gross motor skills in early childhood at RA Az Zahra Sukahaji. This study uses a classroom action research (CAR) method with a qualitative and quantitative approach. Data were collected through observation, interviews, and documentation to measure the effectiveness of implementing engklek games in learning. The results showed that engklek games made a significant contribution to improving children's balance, coordination, agility, and leg muscle strength. In addition, this game also encourages children to be more active in social interactions and increases their independence and confidence in playing. Thus, the application of engklek games in learning activities can be an effective alternative method in developing gross motor skills in early childhood. This study recommends the integration of traditional games into the early childhood education curriculum to improve children's physical and social development as a whole.